2020
DOI: 10.1038/s41387-020-00140-1
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte ω-3 polyunsaturated fatty acids are inversely associated with the risk of oral cancer: a case-control study

Abstract: Objectives Evidence about ω-3 polyunsaturated fatty acids (ω-3 PUFAs) and oral cancer risk were limited. We aimed to evaluate the association of erythrocyte ω-3 PUFAs with the risk of oral cancer in a population from China. Methods Erythrocyte ω-3 PUFAs of 236 oral cancer patients and 300 controls were determined by gas chromatography. Restricted cubic spline and logistic regression were used to analyze the association between erythrocyte ω-3 PUFAs and oral cancer risk. The crude and adjusted OR with 95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“… 72 Another case-control study of 236 oral cancer patients and 300 controls reported a higher level of erythrocyte membrane fatty acids (a proxy for dietary fatty acid intake) in the control group, and found that the association between fatty acid levels and cancer was stronger in NSND patients, further supporting that dietary factors can affect cancer risk in NSND populations. 73 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 72 Another case-control study of 236 oral cancer patients and 300 controls reported a higher level of erythrocyte membrane fatty acids (a proxy for dietary fatty acid intake) in the control group, and found that the association between fatty acid levels and cancer was stronger in NSND patients, further supporting that dietary factors can affect cancer risk in NSND populations. 73 …”
Section: Resultsmentioning
confidence: 99%
“…72 Another case-control study of 236 oral cancer patients and 300 controls reported a higher level of erythrocyte membrane fatty acids (a proxy for dietary fatty acid intake) in the control group, and found that the association between fatty acid levels and cancer was stronger in NSND patients, further supporting that dietary factors can affect cancer risk in NSND populations. 73 In summary, while environmental factors certainly play a role in the development of OCSCC in NSND, more work is needed to determine the contributions of these various factors to oral tumorigenesis and their interactions with smoking and alcohol.…”
Section: Other Factorsmentioning
confidence: 99%
“…A hospital-based case-control study was conducted with patients from the First Affiliated Hospital of Fujian Medical University from September 2013 to December 2020 in Fujian Province, China, as previously described [ 23 ]. Patients with newly diagnosed oral cancer (C00-C07 corresponding to the 10th revision of the International Classification of Diseases) were enrolled in this study and serum samples were collected at admission.…”
Section: Methodsmentioning
confidence: 99%
“…A hospital-based case-control study was conducted with patients from the First A liated Hospital of Fujian Medical University from September 2013 to December 2020 in Fujian province, China, as previously described (23). Patients newly diagnosed with oral cancer were enrolled in this study and serum samples were collected at admission.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%
“…The samples were kept at -80°C until they were analyzed. Details of the erythrocyte membrane FA acquisition and measurement have been described previously (23). In brie y, FA methyl esters were separated using an Agilent 7890B gas chromatograph (Agilent, Palo Alto, CA, USA) equipped with DB-23 fame column (60 m ×0.25 mm inside diameter, the lm thickness of 0.15μm) ame ionization.…”
Section: Measurement Of Fa Pro Le Of Erythrocytes Membrane and Calcul...mentioning
confidence: 99%